Personality traits as predictors of the affective state in patients after breast cancer surgery - Novakov, Ivana; Popovic-Petrovic, Svetlana (Archive of Oncology, 2017)
Background. Breast cancer diagnosis is an extremely stressful life event that brings a number of physical and psychological challenges. Studies show that there is a high prevalence of psychological distress and symptoms of anxiety and depression among the diagnosed individuals. Although it is known that personality traits are strong predisposing factors for elevated experience of distress, research in oncology continues to be more focused on disease-related variables. In order to explore the role of personality traits in the experience of distress, the aim of our study was to examine the predictive value of personality characteristics such as neuroticism, hope, and optimism regarding the affective state of the patients after breast cancer surgery. Methods. The study was conducted on 40 women who had undergone breast cancer surgery, aged from 33 to 69 years (M = 55.02, SD = 9.18). The participants completed the following measures: Basic Demographic Data Questionnaire, The Positive and Negative Affect Schedule (PANAS), Life Orientation Test – Revised (LOT-R), Adult Hope Scale (AHS) and Neuroticism subscale from Big Five Inventory (BFI). Results. Two multiple regression analysis were performed, with the participants' age, level of hope, optimism and neuroticism as predictors and positive/negative affect as the criteria variables. In the first analysis, a statistically significant model was obtained (F (4, 35) = 3.05, p = .03), with optimism being the only significant predictor of positive affect. The second analysis also yields a statistically significant model (F (4, 35) = 3.32, p = .02), where neuroticism, and, marginally, optimism turned out to be significant predictors of negative affect. Conclusion. Our study showed that optimism and neuroticism may be important predictors of the affective state after breast cancer surgery. Therefore, it is important to include these factors in the screening batteries for early detection of vulnerable individuals and to take them into account when planning psychological interventions.
Keywords: Affect; Hope; Neuroticism; Optimism; Personality; Breast cancer